2020
DOI: 10.1108/mbe-08-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Analytical hierarchy process and TOPSIS for selecting best parameters of green manufacturing

Abstract: Purpose Competition and globalization in the today’s scenario have posed many pressures on all manufacturing enterprises either it be small or medium scale organizations but at different levels. The purpose of this paper is to comprehend the usage of comparison for rankings between analytical hierarchy process (AHP) and technique for order of preference by similarity to ideal solution (TOPSIS) approach and find out best parameters, which is a multi-decision-making method for quantifying the implementation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Because the specific experimental data were obtained, the TOPSIS analysis based on the entropy weight method and using the dimensions of energy, economy and environment was adopted to eliminate the interference of scoring; the results are helpful for enterprises to comprehen-sively consider and make decisions. Singh et al [30] adopted AHP and TOPSIS methods to compare and analyze the drivers that promote green manufacturing implementation in small and medium-sized manufacturing enterprises in India, and concluded that green supply chain management, customers' attributes, organizational practices and adoption of new/supportive technology in the organizations are dominant parameters to ensure the successful implementation of green manufacturing practices. Ali et al [31] collected relevant data of 288 SMEs in China and applied structural equation modeling with partial least squares to analyze the obtained receipts.…”
Section: Drivers Of Sustainable Precision Manufacturingmentioning
confidence: 99%
“…Because the specific experimental data were obtained, the TOPSIS analysis based on the entropy weight method and using the dimensions of energy, economy and environment was adopted to eliminate the interference of scoring; the results are helpful for enterprises to comprehen-sively consider and make decisions. Singh et al [30] adopted AHP and TOPSIS methods to compare and analyze the drivers that promote green manufacturing implementation in small and medium-sized manufacturing enterprises in India, and concluded that green supply chain management, customers' attributes, organizational practices and adoption of new/supportive technology in the organizations are dominant parameters to ensure the successful implementation of green manufacturing practices. Ali et al [31] collected relevant data of 288 SMEs in China and applied structural equation modeling with partial least squares to analyze the obtained receipts.…”
Section: Drivers Of Sustainable Precision Manufacturingmentioning
confidence: 99%
“…The manufacturing sector has been facing threat, as well as opportunities with the interest of the customers bending toward technology advancement and environment-friendly techniques, especially in SME's. Many new technology may lead to successfully implementing the eco-friendly manufacturing process Singh et al (2020aSingh et al ( , 2020b.…”
Section: Contribution Of Green Manufacturingmentioning
confidence: 99%
“…Customers can be the driving force that can pressurize the organizations to implement GM. There is a need for organizations to realize that customers' always expect for their better performance of the goods along with high brand value Singh et al (2020aSingh et al ( , 2020b. Customers are dynamically changing their demands with asking for customized features in the products.…”
Section: Contribution Of Green Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations